Analisis Kinerja Petugas Apron Movement Control (AMC) Dalam Penanganan Foreign Object Debris (FOD) di Bandar Udara Mopah Merauke - Christian Fernando Ly; Dhiani Dyahjatmayanti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Airside Foreign Object Debris (FOD) management plays a crucial role in ensuring flight safety, given that FOD can cause serious damage to aircraft and threaten the safety of passengers and crew. Mopah Merauke Airport, located in a swampy area with frequent windy weather and prone to flooding, poses a higher risk of FOD accumulation, thus requiring optimal performance from AMC officers. This study aims to determine the performance of AMC officers in handling FOD to ensure safety in the airside area of Mopah Merauke Airport and to identify obstacles and solutions implemented to overcome these obstacles. This study used a descriptive qualitative approach. Data sources were obtained through in-depth interviews with the Head of the AMC Unit, AMC Supervisor, and Senior AMC, as well as direct observation of FOD handling activities on the apron. Documentation in the form of photographs of FOD found on the apron served as supporting evidence. Data collection techniques used included semi-structured interviews, participant observation, and supporting documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Triangulation of sources and techniques was used to test the credibility of the data. This research was conducted between January and February 2025. The results indicate that the performance of AMC officers in handling FOD has been good, reflected in the disciplined implementation of routine inspections, the use of adequate supporting equipment, a quick response in securing FOD, and the initiative to assist colleagues to ensure the apron is always clean. However, challenges remain, including low awareness among third-party workers regarding cleanliness, environmental conditions that facilitate FOD accumulation, and limited personnel. To address these issues, efforts have been made to optimize patrol schedules, utilize additional equipment, strengthen cross-unit coordination, and request additional personnel to maximize FOD supervision. Thus, FOD handling at Mopah Merauke Airport can be continuously improved to ensure the safety of flight operations.